1991
DOI: 10.1136/bjo.75.8.476
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of intraocular irrigating solutions on the corneal endothelium in intraocular lens implantation.

Abstract: We conducted a randomised prospective controlled study to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…This is consistent with data obtained in studies from Edelhauser et al ,6 7 Matsuda et al 8 and Yagoubi et al ,23 which demonstrated that the corneal endothelium can be better preserved by using solutions with a composition similar to that of aqueous humour.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with data obtained in studies from Edelhauser et al ,6 7 Matsuda et al 8 and Yagoubi et al ,23 which demonstrated that the corneal endothelium can be better preserved by using solutions with a composition similar to that of aqueous humour.…”
Section: Discussionsupporting
confidence: 91%
“…However, just BSS Plus has magnesium, sodium phosphate, sodium bicarbonate, dextrose and glutathione, which are also present in aqueous humour. The rationale for the above-mentioned composition differences that theoretically favour BSS Plus would be: magnesium is essential for the Mg-ATPase endothelial pump; the addition of dextrose would be justified as a natural energy source for endothelial cells24, sodium phosphate and bicarbonate are physiological buffers found in aqueous humour,25 26 and glutathione is a peptide which is important as an antioxidant and as an agent maintaining the intercellular junctions 5 7 8 14 21. In addition, aqueous humour, BSS Plus and Lactated Ringer's pH and osmolarity are 7.38/304; 7.40/305 and 6.4/260, respectively 7 14 21 27.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The radicals and photons may contribute to the mechanism leading to corneal endothelial damage. In vivo studies [42][43][44][45][46][47][48] confirm the importance of the chemical composition of irrigating solutions on postoperative corneal thickness and endothelial cell count. Edelhauser et al 31,43 show that the composition of the irrigating solution is more important to endothelial survival than the irrigation time.…”
Section: Discussionmentioning
confidence: 82%
“…48 Studies using corneal tissue test chambers found that corneal endothelium appeared healthier, with a higher density, if the irrigating solution contained glutathione, 43,46,47 and other studies support the protective effect of glutathione on corneal endothelial cells. 21,42 In in vitro studies, 49 we recently determined that the effective concentrations of oxidized and reduced glutathione required to eliminate the hydroxyl radical signal are on the order of 10 À2 M.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation